2012
DOI: 10.3109/14767058.2012.712305
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine citrate: when and for how long. A literature review

Abstract: The efficacy of caffeine in an episode of Apnoea of Prematurity (AOP) has been known for over thirty years. Its use over long periods of time has not only found it to be manageable within the field of neonatology, but it has also been found to have other favourable actions, such as reducing the incidence of extubation failure, preventing Bronchopulmonary Dysplasia (BPD), reducing the need for Patent Ductus Arteriosus treatment and the beneficial effect it has on Retinopathy of Prematurity. Recent in vitro tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 23 publications
1
24
0
1
Order By: Relevance
“…30,31 The common transient side effects attributed to caffeine include tachycardia, hypertension, tremors, vomiting and rarely opisthotonus, hyperglycemia, hypokalemia, etc. 23,45 Acute overdose may result in jitteriness, seizures, hypertonia, hypercalcemia, etc. 1 However, in view of its wide therapeutic index, the adverse effects are relatively minor and the risk-benefit ratio appears extremely negligible.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…30,31 The common transient side effects attributed to caffeine include tachycardia, hypertension, tremors, vomiting and rarely opisthotonus, hyperglycemia, hypokalemia, etc. 23,45 Acute overdose may result in jitteriness, seizures, hypertonia, hypercalcemia, etc. 1 However, in view of its wide therapeutic index, the adverse effects are relatively minor and the risk-benefit ratio appears extremely negligible.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…A literature review in 2012 concluded that caffeine citrate use in premature infants resulted in a significant reduction in BPD incidence with few side effects. 17 …”
Section: Resultsmentioning
confidence: 99%
“…CC is an odorless, bitter-tasting white crystalline powder. Caffeine is used therapeutically to treat episodes of apnea in premature infants (16). Since CC is a highly soluble Biopharmaceutics Classification System (BCS) class–I drug, its rapid dissolution in the oral cavity impedes its taste masking (17).…”
Section: Introductionmentioning
confidence: 99%